Effect of internal friction among unfluidized particles on measuring minimum fluidization velocity and segregation index. Issue 3 (4th March 2023) - Liu, Qing; Gai, Hengjun; Zhu, Quanhong; Hao, Weikang
Abstract: The internal friction among unfluidized particles makes them polymorphic, thus confusing measurements of minimum fluidization velocity ( U mf ) and segregation index ( S ). Such a polymorphic characteristic of the packed bed caused the Δ P b – U g ↑ curve measured subsequently to be poorly reproducible. The poor reproducibility of determining U mf from this curve resulted eventually from the ambiguity in the traditional definition of U mf . It did not clearly indicate which of the many states the particles should be initially packed into before measuring the Δ P b – U g ↑ curve. The internal friction caused it difficult to accurately measure S for low gas velocities. The corresponding stable fluidization states could not be obtained through reducing the gas flow slowly from complete fluidization to these velocities. Some particles lost the capability to move before reaching their stable equilibrium positions. Only some steady states which could not represent the given U g were obtained. Many states of the unfluidized particles were demonstrated to be metastable and belong to the amorphous/glass state. They could not recover/restore themselves after relatively large perturbations.